2019
DOI: 10.1148/radiol.2018180513
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning–based Method for Fully Automatic Quantification of Left Ventricle Function from Cine MR Images: A Multivendor, Multicenter Study

Abstract: To develop a deep learning-based method for fully automated quantification of left ventricular (LV) function from shortaxis cine MR images and to evaluate its performance in a multivendor and multicenter setting. Materials and Methods: This retrospective study included cine MRI data sets obtained from three major MRI vendors in four medical centers from 2008 to 2016. Three convolutional neural networks (CNNs) with the U-NET architecture were trained on data sets of increasing variability: (a) a single-vendor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
119
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 176 publications
(134 citation statements)
references
References 19 publications
3
119
0
2
Order By: Relevance
“…This limitation prevents models to be deployed in the real world and therefore diminishes their impact for improving clinical workflows. To improve the model performance across MR images acquired from multiple vendors and multiple scanners, Tao et al (2019) collected a large multivendor, multi-center, heterogeneous labeled training set from patients with cardiovascular diseases. However, this approach may not scale to the real world, as it implies the collection of a vastly large dataset covering all possible cases.…”
Section: Model Generalization Across Variousmentioning
confidence: 99%
“…This limitation prevents models to be deployed in the real world and therefore diminishes their impact for improving clinical workflows. To improve the model performance across MR images acquired from multiple vendors and multiple scanners, Tao et al (2019) collected a large multivendor, multi-center, heterogeneous labeled training set from patients with cardiovascular diseases. However, this approach may not scale to the real world, as it implies the collection of a vastly large dataset covering all possible cases.…”
Section: Model Generalization Across Variousmentioning
confidence: 99%
“…Deep learning-based approaches have recently demonstrated success with a variety of other image-segmentation tasks, including intracranial hemorrhage segmentation on CT, 19 structural neuroanatomy classification on brain MR imaging, 20 cartilage segmentation on knee MR imaging, 21 and left ventricular volume on cardiac MR imaging. 22 The winner of the 20th International Conference on Medical Image Computing and Computer Assisted Intervention (MICCAI) 2017 challenge for white matter hyperintensity segmentation 23 was based on a U-Net. 24 Therefore, we adopted a deep learning approach, adapting a U-Net convolutional neural network (CNN) architecture for 3D imaging for the task of disease-invariant FLAIR lesion segmentation.…”
mentioning
confidence: 99%
“…In recent years, deep-learning (DL) has become the method of choice for automated image analysis (Lakhani et al, 2018). Radiology studies have reported on application of deep learning in different organs (Lehman et al, 2018;Nam et al, 2018;Tao et al, 2019). Still, the prognostic role of that application remains undefined and further investigation is needed.…”
Section: Introductionmentioning
confidence: 99%